The teaching of social studies - Kochhar, SK. (New Delhi : Sterling publishers ptd, 1989)
The revision of the book has been necessitated due to tremendous changes both in the content and the methodology of teaching social Studies. The scope of the book has been made broad based and comprehensive and the approach practical and functional. Every effort has been made to equip the social Studies teacher with the new concepts, latest teaching procedures and techniques so as to enable him to be a successful teacher of the subject in the present context. The book in its present form amply meets the requirements of the B.Ed. Syllabus of the different universities of the country. It is hoped that the new edition will be well received by the teacher educators, teacher trainees as well as practising teachers.
Keywords: social studies -- study and teaching